TEACHERS PERCEPTION TOWARD USING ENGLISH E BOOK AT MOSLEM BASED SECONDARY SCHOOL MADRASAH TSANAWIYAH (Journal of English Language and Literature Teaching, 2024)
E books have become a prevalent educational tool in today s learning landscape Contrasting traditional books the utilization of e books displays distinct characteristics particularly among educators who are now required to be proficient in technology based teaching methods This research is focused on ascertaining teachers perceptions regarding the implications of employing e books for English instruction at MTs Negeri 1 Bitung The study employs a qualitative approach and involves English instructors from MTs Negeri 1 Bitung Data collection is carried out through observation in depth interview and documentation The collected data was analyzed using the Miles and Huberman theoretical framework as follows; data reduction data display and drawing conclusions verification The findings of this study reveal that e books offer more benefits than drawbacks The advantages of e books include fostering teacher creativity in developing literacy skills innovates teaching and learning practices lightening students academic load learning flexibility enhanced learning process efficiency and facilitating a deeper understanding of the material Conversely the disadvantages encompass distractions potential eye fatigue from screen radiation and the necessity of a network connection < p>
Keywords: TeachersÃƒÆ’Ã†â€™Ãƒâ€ Ã¢â‚¬â„¢ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã‚Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã‚Â¾ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¢ Perception; E-book Media